Disguised Resistance? The Story of Kurt Gerstein - Hébert, Valerie (Holocaust and genocide studies, 2006)
Kurt Gerstein entered the Waffen-SS in 1941 with the intention, he claimed, of sabotaging Nazi crimes. Gerstein insisted that although he would be required to participate in some criminal activities, he could be most effective as a resister if he were to remain in the SS. In this article, the author describes Gerstein’s life and resistance activities and examines the evidence presented in and the results of three legal proceedings that took place following his death in 1945. All three of the proceedings grappled with the problem of judging Gerstein’s actions, which simultaneously served and opposed a criminal regime. The author concludes with an assessment of how we should remember Gerstein’s controversial life.